2019
DOI: 10.3892/or.2019.7320
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑4712‑5p promotes proliferation of the vulvar squamous cell carcinoma cell line A431 by targeting PTEN through the AKT/cyclin D1 signaling pathways

Abstract: The aim of the present study was to screen differentially expressed miRNAs in vulvar squamous cell carcinoma (VSCC), observe the role of microRNA-4712-5p in VSCC and investigate its targets and regulatory mechanism. Differentially expressed miRNAs in human VSCC tissues were screened. microRNA-4712-5p was selected and its expression level was verified in clinical tissue samples and the VSCC cell line A431 by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analysis. The overexpression vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Several miRNAs that are overexpressed in RGCs have been shown to have oncogenic roles in vitro, as well as defined molecular targets that they regulate ( Table 3 ). miR-9 [ 55 ], miR-10a [ 73 ], miR-21 [ 126 ], miR-590-5p [ 108 ], miR-3147 [ 110 ] and miR-4712 [ 109 ] have been described as “oncomiRs” across multiple mammalian cell types, which is consistent with their role in RGCs. In addition, underexpressed miRNAs in RGCs such as miR-34 [ 124 ], miR-126 [ 72 ] and miR-196b [ 125 ] act as tumor suppressors.…”
Section: A Brief Overview On Mirnas and Their Regulated Targets In Rgcsmentioning
confidence: 82%
See 2 more Smart Citations
“…Several miRNAs that are overexpressed in RGCs have been shown to have oncogenic roles in vitro, as well as defined molecular targets that they regulate ( Table 3 ). miR-9 [ 55 ], miR-10a [ 73 ], miR-21 [ 126 ], miR-590-5p [ 108 ], miR-3147 [ 110 ] and miR-4712 [ 109 ] have been described as “oncomiRs” across multiple mammalian cell types, which is consistent with their role in RGCs. In addition, underexpressed miRNAs in RGCs such as miR-34 [ 124 ], miR-126 [ 72 ] and miR-196b [ 125 ] act as tumor suppressors.…”
Section: A Brief Overview On Mirnas and Their Regulated Targets In Rgcsmentioning
confidence: 82%
“…Finally, upregulation of miR-590-5p may promote cellular malignant behavior via the target gene TGFβR II . In another study, there was an increased level of expression of miRNA-4712-5p in VSCC, promoting proliferation and invasion, by affecting PTEN and its downstream p-GSK3β, p-AKT, and cyclin D1 signaling pathways [ 109 ]. It has also been shown that miR-3147 serves as an oncomiR in VSCC via suppression of Smad4 [ 110 ].…”
Section: Dysregulation Of Mirnas In Rare Gynecological Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of miR-4712-5p affects invasion and cell proliferation in vulvar squamous cell carcinoma. In addition, it targets PTEN, reducing its expression, and may affect the PTEN/AKT/p-GSK3β/cyclin D1 signaling pathway, affecting cell proliferation [ 142 ].…”
Section: Role Of Mirnas In Cancer Of the Vulvamentioning
confidence: 99%
“…Targeted therapy is the product of the times with the development of society and science and technology, which is forward-looking (23). Targeted therapy is a molecule-based therapy, which is different from the previous methods of surgery, radiotherapy and chemotherapy based on the cellular and molecular level and through specific oncogenic sites (24). Medical scientists have gradually deepened their understanding of cancer from the parenchymal lesions to cells to the molecular level, and a relatively new and less painful way of targeted therapy has emerged (25).…”
Section: Proliferation and Apoptosis Of Cancer Cells In Different Tis...mentioning
confidence: 99%